Narrating emergence in the curious terrain of academic development research: a realist perspective - Niven, Penelope Mary (Rhodes University, Faculty of Education, Department of Education, 2012)
This dissertation adopts a realist meta-perspective on a body of the scholar's own research papers written between 2005 and 2011, all either published or in press and offered for reference in the Appendices. The six papers represent the point of departure for the thesis; they are the phenomenon for further investigation into 'what must be the case' for the research events to have emerged as they did. One aspect of this study, therefore, is an auto ethnographic account of conducting research in the field of Academic Development within varied settings and over a given time frame. But alongside this personal history it narrates cycles in the Academic Development movement in South Africa over 30 years. Margaret Archer's Social Realist principle of analytical dualism (1995) is used to disaggregate the emergent properties within these histories and to enable an analysis of the underlying mechanisms that generated them. It refers to three social domains. Firstly, it describes the material structures - the institutional environments, policies, roles or professional conditions - in which the projects were conceived. Secondly, it identifies the cultural registers that the profession was drawing on - such as theories, beliefs or discourses. Thirdly, it draws attention to the agency of individuals and communities in the field as they independently activated or mediated these various conditioning structures and registers. So the study is a systematic examination of the parts and the people in research stories, of the complex interrelationship of structural and agential elements, and of how together they have generated particular forms of knowing and kinds of knowledge in Academic Development. Drawing from this 'history-within-a-history', the study makes some claims for 'what must be the case' for substantial knowledge to flourish in a newly emergent, hotly contested and relatively unstable field. It argues that Academic Development has few shared epistemological foundations and boundaries, and its roles and functions are shifting and diverse. It describes the tensions in the field between those who have been inclined to understand it as primarily concerned with redress or equity in the postapartheid state, and yet others who have prioritised Academic Development as an efficiency project within higher education. But there is a third discourse emanating from those in the profession who have consistently argued that neither of these approaches can succeed without drawing on stronger theoretical foundations. This study endorses the view that Academic Developers need to identify more coherent ontological and epistemological frames for their research work. This has important implications for building the kind of substantial knowledge base that could be more influential in addressing the troubled terrain of South African higher education. The study refers extensively to Lewis Carroll's Alice in Wonderland (1865) and Through the Looking-Glass (1871) and to Mervyn Peake's 1946 illustrations of these children's stories, finding in these texts powerful analogies and metaphors for principles in realist philosophy and theory, and for describing a researcher's journey towards a more assured identity in the curious field of Academic Development.
Keywords: Education, Higher -- Aims and objectives -- South Africa; Universities and colleges -- South Africa; Educational change -- South Africa; Black people -- Education (Higher) -- South Africa